Milk production of goats with different tone of the autonomic nervous system - B. I. Boychuk; V. I. Karpovskyi; B. V. Gutyj; I. A. Hryshchuk; A. V. Hryshchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The active development of goat breeding is rapidly moving from small enterprises to large farms. This development is ensured by the rapid growth of demand for these products for ordinary consumers and people looking for an alternative to cow's milk. Therefore, a significant amount of effort is being made to improve the yield of dairy products from goats. This is because this farm cannot rapidly increase the number of livestock, and the demand for this product is constantly growing. Our study aimed to establish the dependence of the autonomic nervous system tone on the indicators of goat milk production. To form the experimental groups of animals, a variational pulse oscillometric study was used to calculate the following indicators: mode (Mo), mode amplitude (AMo), variation range (∆x), autonomic rhythm index (ARI), autonomic balance index (ABI), and tension index (TI). Subsequently, three experimental groups of animals were formed according to the tone of autonomic nervous regulation using the Baevsky method: sympathotonics, normotonics, and vagotonics. Statistical analysis of the results and calculation of Student's t-test to establish correlation and one-factor analysis of variance between milk production and autonomic nervous regulation tone were performed using Microsoft Excel. According to the results of the study, it was found that the highest milk production was determined in the experimental group of normotonics 1058 ± 9.76 l/year (P < 0.001), and the lowest in sympathotonics 845.5 ± 27.71 l/year (P < 0.001). Also, according to the initial data's statistical processing results, a correlation was established between milk production indicators and the tone of autonomic nervous regulation. Thus, the experimental group of normotonics had a correlation r = (-0.649) (P < 0.001), sympathotonics r = (-0.572) (P < 0.001), and vagotonics r = 0.865 (P < 0.001), which is confirmed by one - factor analysis of variance.